Resistance and depression in patients with HIV-AIDS - Delgado Arenas, Raul (2017)
The purpose of this research is to determine the relation between the resentment and depression that happens in HIV and AIDS patients from the Hipolito Unanue Lima Hospital TARGA Program in 2016 especially in the district of El Agustino. The employed standpoint was the quantitative and the method was deductive hypothetical. The gathering technique was conducting a survey and the resource was Resentment Test which was made by Leon, Romero and Beck Depression Inventory (BDI-II). To sum it up, there is a low significant relation between the resentmen